The Financial determinants of integrated reporting disclosure by Jordanian companies - Hamzeh Al Amosh; Saleh F. A. Khatib; Khaled Hussainey (Journal of Risk and Financial Management, 2022)
The paper aims to investigate the effect of financial leverage, profitability, liquidity ratios, cash holdings, and interest coverage ratios on the level of integrated reporting disclosure-as one of the reports that promotes sustainable development-of Jordanian industrial listed companies. The content analysis method was used to analyze the annual reports of 51 listed Jordanian industrial companies during the years from 2014 to 2019 (306 firm-year observations). The analysis showed that financial leverage, profitability, liquidity and cash holdings are important determinants for integrated reporting, whereas the analysis did not support the effect of the interest coverage ratio. To the best of our knowledge, this is the first empirical study that deals with the impact of a set of financial variables on integrated reporting in the context of emerging countries such as Jordan. This is also the first study that deals with disclosing integrated reports through the perspective of shareholders and stakeholders, as integrated reporting contains two parts, financial and non-financial; therefore, the current study contributes to the disclosure literature by providing new theoretical and empirical evidence in the context of emerging markets.
Keywords: 650; sustainability; leverage; cash holding; corporate disclosure; integrated reporting; Jordan